Recycled water for non-potable use: Understanding community perceptions and acceptance in Malaysia - Nur Aina Bachi'; Wan Hanna Melini Wan Mohtar; Wan Zawiah Wan Zin; Haruka Takeuchi; Zarimah Mohd Hanafiah (Water Policy, 2023)
Sustainable water supply is one of the key issues for water resources management. The future demand for clean water is putting pressure on the Malaysian government to find alternative supplies and best management practices in managing water resources, such as the use of reclaimed water. This paper evaluates the perceptions and acceptance of the use of treated water for non-drinking purposes in Malaysia from the responses of 1,004 participants. The results show that age and level of education play an important role in the level of community acceptance. Females tend to be more selective than males in their acceptance to use reclaimed water. To guarantee that the public receives accurate information about reclaimed water, social media can be used for disseminating information, especially to younger generations. HIGHLIGHTS Reclaimed water is one of the options to reduce the impact of climate change.; High levels of daily water consumption give impact dependence on clean water in the future.; The level of education is able to influence the community's acceptance of using reclaimed water.; Water supply disruptions cause consumers to seek alternative ways, such as the use of reclaimed water.; Social media help in imparting information.;